Are Mediterranean Island Mountains Hotspots of Taxonomic and Phylogenetic Biodiversity? The Case of the Endemic Flora of the Balearic Islands - Moisès Guardiola; Llorenç Sáez (Plants, 2023)
The Mediterranean islands are exceptionally rich in endemism, most of which is narrowly distributed. Conservation measures, such as protected areas, have been prioritised, mainly on the basis of species richness and endemism, but phylogenetic information should also be taken into account. In this study, we calculated several taxonomic and phylogenetic metrics at a high resolution for the endemic flora of the Balearic Islands (154 taxa), in order to identify (i) the spatial patterns and environmental factors that explain this endemism, (ii) hotspots of species and phylogenetic endemism, and (iii) gaps in the protected areas. The taxonomic and phylogenetic metrics showed different distribution patterns, but the mountainous areas of Mallorca, and some coastal areas of the Balearic Islands, have the highest values. These values were positively related to elevation, precipitation, temperature, and slope, and negatively related to the distance from the coast, aspect, and the temperature of the wettest quarter. We identified top grid hotspots where all the metrics had the highest values, and we also identified nano-hotspots within these hotspots, in some of the highest peaks of Mallorca, where most of these metrics’ maximum values coincided. This approach allowed us to identify some gaps in the conservation priority areas, and to highlight the need to review their boundaries and definition.